Feminist Activism in Digital Culture: Problems of Class and Ethics - Muria Endah Sokowati (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
Social media is a platform used by feminist activists for activism. It overcomes spatial and temporal barriers, and helps spread the movement's message more quickly and efficiently. The participatory culture encourages the feminist movement to develop more massively. Many argue that social media helps feminist activists to empower women. Related to the statement, this study observes how activism practices in social media represent women's voices and problems. This study also seeks to reveal the problems in the movement. The researcher observed five accounts of feminist activists on Instagram (@Indonesiafeminis, @lawanpatriarki, @perempuanfeminis, @muslimahfeminis, @perempuan.merdeka). Through the virtual ethnography method, the researcher found a representation problem when digital feminist accounts published the problems experienced by women through their content. These accounts only represent middle-class women's problems. There is also an ethical problem because these accounts tend to be reactive by ignoring the ethics of doing activism.